Financial Openness and Financial Development: Evidence from Emerging Countries - Mehmet Umutlu; Melis Gultekin; Hakan Özkaya (Istanbul Business Research (IBR), 2020)
We investigate the potential relation between financial openness and financial development for 27 emerging countries for the period between 1996 and 2016. We focus on three dimensions of financial openness: capital account openness, trade openness, and stock-market openness. In this study, we propose alternative measures for capital account and trade openness. Moreover, we offer capital flow and valuation-based measures for stock-market openness as a potential determinant of financial development. Our findings indicate that capital account openness and trade openness are the key drivers of financial development. These results are not sensitive to the use of alternative financial openness and financial development measures, and are robust after being controlled for institutional quality and its components. Our results have implications for policymakers in emerging countries who try to increase the depth of their financial markets for an easier and cheaper access to funds.
Keywords: 650; Financial Development; Trade Openness; Capital Account Openness; Stock Market Openness